The role of nitric oxide, insulin resistance, and vitamin D in cognitive function of older adults - Nakhaee, Samaneh; Azadi, Rasul; Salehinia, Hamid; Moodi, Mitra; Zarban, Asghar; Sharifi, Farshad; Khorashadizadeh, Masoumeh; Farrokhfall, Khadijeh (Scientific reports, 2024)
Aging is accompanied by possible cognitive impairment, as well as a reduction in nitric oxide (NO) bioavailability, insulin resistance, and vitamin D deficiency. Among these Nitric oxide exhibits a dual role in brain biology, where both low and high levels can have detrimental effects on memory and neurotoxicity. In this study we aimed to investigate the role of nitric oxide, insulin resistance, and vitamin D in cognitive function of elderly individuals. This case-control study involved participants aged ≥ 60 years who were under observation in the Birjand Longitudinal Aging Study. A total of 40 participants were selected as controls, while 64 participants with cognitive impairment were identified as cases. The cases were further subdivided according to their Mini-Mental State Examination (MMSE) scores into two groups: mild and moderate cognitive impairment. Cognitive function in both cases and controls was assessed using the MMSE. The levels of total NOx, vitamin D, insulin, and blood glucose were measured using ELISA and spectrophotometric immunoassays. Insulin resistance indices, such as homeostasis model assessment of insulin resistance (HOMA-IR) and quantitative insulin sensitivity check index (QUICKI) were calculated. Serum NOx levels were significantly lower in participants with cognitive impairment compared to the control group ( p < 0.01). However, the mean (SD) levels of serum vitamin D, insulin, and glucose, as well as the insulin resistance markers, showed no significant differences between the groups. A positive correlation was observed between serum NOx levels and MMSE scores. NO may be an essential factor for normal brain function, as serum NOx levels were significantly higher in controls compared to those with cognitive impairment, and there was a positive correlation with MMSE scores. Other metabolic and nutritional markers, including vitamin D and insulin resistance, did not demonstrate a significant effect.